Female Genital Mutilation and Obstetric Outcomes in the Far-North Region, Cameroon: A Case - Control Study - G. E. Halle-Ekane; N. M. N. Guidona; L. T. Mbuagbaw; A. M. Mengouo; R. E. Mbu (Archives of Current Research International, 2019)
Various forms of Female Genital Mutilations (FGMs) have been performed for several years and continue to be practiced with serious consequences. Aims: The study aimed at assessing the socio-demographic profile, prevalence, types of FGM, and associated obstetric outcomes in the Far North Region, Cameroon. Study Design: Case-control study. Place and Duration of Study: Four health facilities in the aforementioned region from 4th February, 2017 to 28th April 2017. Methods: We included 213 parturients matched for age and parity in a proportion of 1:2 (71 with FGM and 142 counterparts). Data was collected on their socio-demographic characteristics, knowledge of FGM and obstetric outcomes. Each parturient’s labor was monitored using a partograph and intermittent fetal heart rate auscultation. The mother-neonate dyads were followed up until discharge from the hospital. Data were analyzed using Epi Info™ version 7. Results: The mean age of parturients was 23.8 years (SD: 5.8 years). The prevalence of FGM was 28.7%. Most participants had FGM before the age of ten for the following reasons: cultural, marital, social acceptability and suppression of sexual desires. Female genital mutilation was significantly associated with Caesarian section (RR:2.91; 95% CI: 1.43-5.93; p=0.002), episiotomy (RR 8.0: 95% CI 1.56-17.26) P=0.03), perineal tears (RR: 3.67; 95% CI: 1.93-6.98; p<0.001), prolonged labor (RR:2.7; 95% CI 1.44-5.09; p<0.001), and neonatal resuscitation (RR:.44; 95% CI: 1.59-12.18; p=0.002). However, only perineal tears (Adjusted RR:5.58; 95% CI: 2.49-12.53; p<0.001) and episiotomy (Adjusted RR 11.52; 95% CI: 1.16-114.69; p= 0.03) were independently associated with FGM on multivariate analysis. Conclusion: The prevalence of FGM was high. FGMs were associated with maternal and fetal morbidity. Therefore, mass sensitization on the consequences of FGM, utilization of ANC services and health facility child births should be encouraged.